e-clustering - an innovative approach for economic policy - Ute Hansen (European Regional Science Association (ERSA), 2004)
In the State of Schleswig-Holstein the strategy of economic policy is based on a concept which is known as “Cluster Building”. An economic cluster initiates the networking of all participants in a value-added chain. The objective is to bundle the potentials and competences for increasing the innovation power and competitiveness of the partners in a cluster. Because of internet-technology, business and government networking in a rural area will obtain a driving force. Internet-technologies, like infrastructure, applications, platforms, broadband, enable the business processes between companies, research institutes and government to be networked. eBusiness and eGovernment/eAdministration will cause a fundamental structural change of the private and public sector. Owing to this development, there is a new demand for Economic Policy and Technology Policy. With the strategy of eClustering this demand is taken into account. The partners in an eCluster are networked by processes which are more and more standardised and so able to be supported by online-applications. An eCluster needs a central infrastructure and services. Knowledgemanagement, eLearning, eMarketplaces, personnel management and last but not least eGovernment are the main processes and services of an eCluster. Funding activities focuses on innovative eClustering-projects in the State of Schleswig-Holstein: They should on the one hand increase the demand for broadband infrastructure and services and therewith for the regional development of TIMES (Telecommunication, Information Technology, Multimedia, Entertainment, Security) and on the other hand support networking and eBusiness.
Keywords: 330